Field emission from oriented tin oxide rods - Deshpande, A. C.; Koinkar, Pankaj M.; Ashtaputre, S. S.; More, Mahendra A.; Gosavi, S. W.; Godbole, P. D.; Joag, Dilip S.; Kulkarni, S. K. (Thin Solid Films, 2006)
Tin oxide (SnO2) films were grown on silicon substrates by a wet chemical route. It was found from scanning electron microscopy investigations that oriented SnO2 rods normal to the substrates were obtained. Field emission studies were carried out in diode configuration in an all metal ultra high vacuum chamber at a base pressure similar to 1.33 x 10(-8) mbar. The `onset' field required to draw 0.1 mu A/cm(2) current density from the emitter cathode was found to be similar to 3.4 V/mu m for SnO2 rods. The field emission current and applied field follows the Folwer-Nordheim relationship in low field regime. The observed results indicate that the field emission characteristics of chemically grown SnO2 structures are comparable to the vapor grown nanostructures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: field emission; microstructures; scanning electron microscopy; tin oxide

Field emission studies of novel ZnO nanostructures in high and low field regions - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S.; Pillai, Vijayamohanan K. (Nanotechnology, 2006)
A study of the field emission characteristics of novel structures of ZnO, namely marigolds, multipods and microbelts, has been carried out in both the close proximity configuration and the conventional field emission microscope. The use of a conventional field emission microscope overcomes the drawback of arc formation at high field values. The nonlinearity in the Fowler - Nordheim ( F - N) plot, a characteristic feature of semiconductors has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability exhibited by these structures is also promising for future device applications.

ZnO multipods, submicron wires, and spherical structures and their unique field emission behavior - Ramgir, Niranjan S.; Late, Dattatray J.; Bhise, Ashok B.; More, Mahendra A.; Mulla, Imtiaz S.; Joag, Dilip S.; Vijayamohanan, K. (Journal of Physical Chemistry B, 2006)
A simple method of vapor deposition for the shape selective synthesis of ZnO structures, namely, multipods, submicron wires, and spheres, has been successfully demonstrated. A plausible growth mechanism based on the studies of scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) is proposed. Our studies suggest that the growth of a multipod structure is governed by the screw dislocation propagation while the vapor-liquid-solid (VLS) mechanism is responsible for the formation of submicron wires and spheres. Moreover, the flow rate of the carrier gas plays a crucial role in governing the morphology. Further, these structures exhibit an enhanced field emission behavior. The nonlinearity in the Fowler-Nordheim (F-N) plot, a characteristic feature of electron emission from semiconductors, is explained by considering the contributions from both the conduction and the valence bands of ZnO.

Energy analysis of field emitted electrons from a ZnO tetrapod - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Ramgir, Niranjan S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Applied Physics Letters, 2007)
The experimental total energy distribution (TED) of the field emitted electrons from a single pod of a ZnO tetrapod has been obtained, exhibiting a two-peak feature. The energy difference between the two peaks in the TED is found to be nearly equal to the band gap of the bulk ZnO. The results show that field emitted electrons originate from both the conduction and valence bands. The peak position dependence on the applied voltage has also been observed. In the present case, the size of the ZnO tetrapod is not small enough to reflect the quantum confinement effects.

Field emission investigations of RuO2-doped SnO2 wires - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Applied Surface Science, 2007)
Field emission studies of a bunch and a single isolated RuO2:SnO2 wire have been performed. A current density of 5.73 x 10(4) A/cm(2) is drawn from the single wire emitter at an applied field of 8.46 x 10(4) V/mu m. Nonlinearity in the Fowler-Nordheim (F-N) plot has been observed and explained on the basis of electron emission from both the conduction and the valence bands of the semiconductor. The current stability recorded at the preset value of 1.5 LA is observed to be good. Overall the high emission current density, good stability and mechanically robust nature of the RuO2:SnO2 wires offer advantages as field emitters for many potential applications. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emission; field enhancement factor; RuO2; SnO2

Enhanced field emission from hexagonal rhodium nanostructures - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Late, Dattatray J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2008)
Shape selective synthesis of nanostructured Rh hexagons has been demonstrated with the help of a modified chemical vapor deposition using rhodium acetate. An ultralow threshold field of 0.72 V/mu m is observed to generate a field emission current density of 4 x 10(-3) mu A/cm(2). The high enhancement factor (9325) indicates that the origin of electron emission is from nanostructured features. The smaller size of emitting area, excellent current density, and stability over a period of more than 3 h are promising characteristics for the development of electron sources. (C) 2008 American Institute of Physics.

RuO(2) doped SnO(2) nanobipyramids on Si (100) as a field emitter - Bhise, Ashok B.; Late, Dattatray J.; Ramgir, Niranjan S.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Thin Solid Films, 2008)
Thin films of RuO(2): SnO(2) nanobipyramids have been grown on silicon (100) flat substrates, and their field emission behavior has been investigated. The field emission experiments have been performed in parallel plate configuration. In this experiment, the onset field for 0. 1 gA/ cm 2 current density has been found to be 0.2 V/mu m. The Fowler-Nordheim plot shows non-linear nature typical that of a semiconductor. The field enhancement factor has been estimated to be 35,600 cm(-1), indicating that the field emission originates from the nanometric features of the emitter. The current stability recorded at a preset value of I tA is observed to be good. Our field emission results on RuO(2): SnO(2) nanobipyramids indicate that, RuO(2): SnO(2) nanobipyramids are a potential candidate for futuristic field emission based devices. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: doped semiconductor; field emitter; field enhancement factor; ruthenium oxide; tin oxide

Scanning tunneling microscopic and field emission microscopic studies of nanostructured molybdenum film synthesized by electron cyclotron resonance plasma - Purohit, Vishwas S.; Bhise, Ashok B.; Dey, Shirshendu; More, Mahendra A.; Dharmadhikari, C. V.; Joag, Dilip S.; Pasricha, Renu; Bhoraskar, S. V. (Vacuum, 2008)
Cathodic sputtering is demonstrated to be effective in synthesizing thin films of molybdenum nanoparticles. An electron cyclotron resonance plasma reactor has been used as the source. The particle size distribution is found to be controllable by proper choice of the cathodic bias potential. Sizes ranging between 20 and 30 nm deposited at the optimum bias potential are found to exhibit a self assembled structure as observed by scanning tunneling microscopy. Field emission microscopic studies on these films supported on W have exhibited very stable emission current over a period of 3 h. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: ECR plasma; Field emission microscopy; Hollow cathode chemical sputtering; Mo nanoparticles; Scanning tunneling microscopy

Field emission investigation of single Fe-doped SnO2 wire - Bhise, Ashok B.; Late, Dattatray J.; Sathe, Bhaskar R.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Solid State Sciences, 2009)
Tin oxide submicronwires doped with Fe element were prepared by the thermal evaporation method. Morphological and structural characterizations revealed wires with sub micron size and crystalline in nature. The field electron emission from the single Fe:SnO2 wire was carried out in conventional field emission microscope. The Fowler-Nordheim plot obtained from I-V characteristics of the wire showed a linear behavior typical that of metal. The field enhancement factor estimated from the slope of the F-N plot is 7455 cm(-1), indicating that the field emission is from nanometric features of the emitter. A current density of 10 A/cm(2) has been obtained at an applied field of 4.845 x 10(3) V/mu m. The field emission current-time record at a current level of 1 mu A for more than 3 h duration is promising for various field emissions based applications. (C) 2009 Published by Elsevier Masson SAS.
Keywords: Current stability; Fe doped; field emission; SnO2

Field emission properties of Al-doped ZnO nanostructures - Navale, Shalaka C.; Sheini, Farid Jamali; Patil, Sandip S.; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A.; Gosavi, Suresh W. (Journal of Nano Research, 2009)
Field emission from Al-doped ZnO nanostrcutures has been investigated in planar diode configuration under ultra high vacuum conditions. The Al-doped ZnO nanostructures were synthesized by co-precipitation method with varying aluminium concentrations. The as- synthesized product was characterized by x-ray diffraction, scanning electron microscope and energy dispersive x-ray analysis. The threshold field required to draw a current density of similar to 1 mu A/cm(2) was observed to be similar to 2.0 V/mu m and similar to 2.3 V/mu m for Al-doped ZnO nanostructures synthesized with aluminium concentrations of 1% and 3%, respectively. The Fowler- Nordheim (F-N) plots for both the specimens exhibit non-linear behaviour, which is observed to be specimen dependent. The nonlinearity observed in the F-N plots has been interpreted on the basis of the theory of electron emission from semiconductor emitters. The field enhancement factors, estimated from the slope of the F-N plots, are found to be similar to 9.3 x 10(3) and 3.9 x 10(3) for 1% and 3% Al-doped ZnO emitters, respectively. The high values of the field enhancement factor Suggest that the emission is from the nanostructures. The emission current stability measured at the preset value of similar to 2 mu A over a period of more than three hours is found to be fairly stable. The results indicate use of Al-doped ZnO nanostructures as promising emitters for field emission based devices.
Keywords: field emission; Fowler-Nordheim plots; Nanostructures; ZnO

Influence of process variables on growth of ZnO nanowires by cathodic electrodeposition on zinc substrate - Sheini, Farid Jamali; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A. (Thin Solid Films, 2009)
Influence of the deposition duration and electrolyte concentration on the structural and morphological features of the ZnO thin films, grown by cathodic electrodeposition on zinc substrate followed by annealing in air at 400 degrees C, have been investigated. The surface morphology of the as-synthesized films shows two distinct features, presence of `2-dimensional nanosheets' on the area near the electrolyte-air interface and `granular' nanostructures, below the interface region. However, upon annealing, the formation of ZnO nanowires, possessing length of several microns and diameter less than 20 nm, on the entire substrate is observed. The X-ray and selected area electron diffraction patterns clearly confirm the polycrystalline nature of the ZnO nanowires. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Annealing; Electrodeposition; Nanowires; photoluminescence; scanning electron microscopy; transmission electron microscopy; Zinc oxide

Fabrication of In-doped SnO2 nanowire arrays and its field emission investigations - Bhise, Ashok B.; Late, Dattatray J.; Sathe, B.; More, Mahendra A.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K.; Joag, Dilip S. (Journal of Experimental Nanoscience, 2010)
The field emission of In-doped SnO2 wire array has been performed in parallel plate diode configuration. A maximum current density of 60 mu A/cm2 is drawn from the emitter at an applied field of 4 V/mu m. The nonlinearity in the Fowler-Nordheim plot, characteristics of semiconductor emitter has been observed and explained on the basis of electron emission from both the conduction and the valence bands. The current stability recorded at a preset value of 1 mu A is observed to be good. The high emission current density, good current stability and mechanically robust nature of the wires offer unprecedented advantages as promising cold cathodes for many potential applications based on field emission.
Keywords: cold cathodes; device; Doping; field emission; Nanowires; SnO2

Fowler-nordheim plot behavior and mechanism of field electron emission from ZnO tetrapod structures - Al-Tabbakh, Ahmed A.; More, Mahendra A.; Joag, Dilip S.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (ACS Nano, 2010)
Field emission measurements of current-voltage characteristics are reported for tetrapod structures of ZnO. The nonlinear Fowler-Nordheim (FN) plot is analyzed according to a model of calculation based on saturation of conduction band current and predominance of valence band current at high-field values. The simulated FN plot exhibits similar features to those observed experimentally. The model of calculation suggests that the slope variation of the FN plot, in the high-field and low-field regions, does not depend on the magnitude of saturation. Instead, it is a characteristic of the energy band structure and voltage-to-barrier-field conversion factor of the emitting material.
Keywords: field emission; Fowler-Nordheim plot; Nanostructures; nonlinearity; ZnO

High current density, low threshold field emission from functionalized carbon nanotube bucky paper - Kakade, Bhalchandra A.; Pillai, Vijayamohanan K.; Late, Dattatray J.; Chavan, Padmakar G.; Sheini, Farid J.; More, Mahendra A.; Joag, Dilip S. (Applied Physics Letters, 2010)
Field emission studies of bucky paper of multiwalled carbon nanotubes (MWNTs), prepared after microwave (MW) assisted acid functionalization are reported along with a comparison with that of ``as-grown'' sample. MW treated bucky papers reveal an interesting linear field emission behavior in Fowler-Nordheim plot. The field emission currents at preset value are found to be remarkably stable over a period of more than 3 h sustaining current densities of 4.9 mA/cm(2) and 8.5 mA/cm(2) for ``as-grown'' and functionalized sample, respectively. The enhancement in the field emission due to functionalization has been discussed in terms of tip opening and defect induced charge transport caused by intershell and intertubular interaction. (C) 2010 American Institute of Physics. [doi:10.1063/1.3479049]
Keywords: Carbon nanotubes; current density; field emission; fullerenes

Observation of photoconductivity in Sn-doped ZnO nanowires and their photoenhanced field emission behavior - Sheini, Farid Jamali; More, Mahendra A.; Jadkar, Sandesh R.; Patil, K. R.; Pillai, Vijaymohanan K.; Joag, Dilip S. (Journal of Physical Chemistry C, 2010)
Sn-doped ZnO nanowire films have been Successfully synthesized by electrodeposition oil zinc foil followed by annealing in air at 400 degrees C for 4 h. The XRD patterns of the annealed specimens exhibit I set of well-defined diffraction peaks indexed to the wurtzite phase of ZnO. The Surface morphology of the as-synthesized films showed a network of densely packed flakes/sheets oil the Substrate. However, upon annealing, the formation of ZnO nanowires, processing length in the range of several micrometers and diameter less than 150 nm, oil the entire substrate is observed. The relative atomic percentage of Sri, estimated from the energy dispersive spectra, was found to be 0.5 and 2.0 in the ZnO films deposited for 10 and 40 min durations, respectively. Front the field emission studies, the Values of the turn-on field and threshold field, required to draw emission Current density of 10 and 100 mu A/cm(2), are observed to be 0.68 and 1.1 V/mu m for 0.5% Sn-doped ZnO and 1.72 and 2.25 V/mu m for 2.0% Sn-doped ZnO, respectively. The field emission Current stability investigated for a duration Of h at the preset value of 100 mu A is found to be excellent. A prominent photoenhancement in the field emission Current upon visible light illumination of the Sn-doped ZnO nanowires films has been observed. This enhancement has been attributed to the photoconductivity of the Sn-doped ZnO.

Synthesis of Cu-ZnO and C-ZnO nanoneedle arrays on zinc foil by low temperature oxidation route: effect of buffer layers on growth, optical and field emission properties - Jamali-Sheini, Farid; Patil, K. R.; Joag, Dilip S.; More, Mahendra A. (Applied Surface Science, 2011)
Different densities of ZnO nanoneedle films have been prepared by pre-coated zinc foils with thin layer of copper and carbon followed by thermal oxidation at 400 degrees C in air. The X-ray diffraction patterns show well defined peaks, which could be indexed to the wurtzite hexagonal phase of ZnO. The scanning electron microscope images clearly reveal formation of ZnO needles on the entire substrate surface. The X-ray photoelectron spectroscopy studies indicate that Cu and C ions are incorporated into the ZnO lattice. Photoluminescence studies evaluate different emission bands originated from different defect mechanism. From the field emission studies, the threshold field, required to draw emission current density of similar to 100 mu A/cm(2), is observed to be 2.25 V/mu m and 1.57 V/mu m for annealed zinc foil pre-coated with copper and carbon, respectively. The annealed film with copper layer exhibits good emission current stability at the pre-set value of similar to 100 mu A over a duration of 4 h. The results show that buffer layer is an important factor to control the growth rate, resulting in different density of ZnO needles, which leads to field emission properties. This method may have potential in fabrication of electron sources for high current density applications. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Buffer layer; Carbon; Copper; field emission; Nanoneedle; ZnO

Synthesis of single crystalline CdS nanocombs and their application in photo-sensitive field emission switches - Chavan, Padmakar G.; Badadhe, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Nanoscale, 2011)
Single crystalline CdS nanocombs were synthesized by a thermal evaporation route. The photo-sensitive field emission current shows a reproducible switching behavior, with a rise in current level of nearly five times the initial preset value of similar to 1 mu A. An ultra low turn-on field, required to draw an emission current density of similar to 0.1 mu A cm(-2) (100 nA), is found to be similar to 0.26 V mu m(-1) (260 V), which is much lower than the reported values for various other CdS nanostructures. Upon illumination with visible light the CdS nanocombs act as a photo field emission switch. At an applied field of similar to 0.65 V mu m(-1) the current densities are observed to be similar to 14.6 mu A cm(-2) and similar to 26.9 mu A cm(-2), without and with light illumination, respectively. The average emission current is seen to be stable over the duration of measurement for two preset values. The high sensitivity and fast response in the visible range indicates that the CdS nanocombs can be used as a photo-sensitive field emitting switch in device applications, and also in pulsed electron beam technology.

Laser synthesized super-hydrophobic conducting carbon with broccoli-type morphology as a counter-electrode for dye sensitized solar cells - Gokhale, Rohan; Agarkar, Shruti A.; Debgupta, Joyashish; Shinde, Deodatta; Lefez, Benoit; Banerjee, Abhik; Jog, Jyoti Prakash; More, Mahendra A.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Nanoscale, 2012)
A laser photochemical process is introduced to realize superhydrophobic conducting carbon coatings with broccoli-type hierarchical morphology for use as a metal-free counter electrode in a dye sensitized solar cell. The process involves pulsed excimer laser irradiation of a thin layer of liquid haloaromatic organic solvent o-dichlorobenzene (DCB). The coating reflects a carbon nanoparticle-self assembled and process-controlled morphology that yields solar to electric power conversion efficiency of 5.1% as opposed to 6.2% obtained with the conventional Pt-based electrode.

Organization of cubic CeO2 nanoparticles on the edges of self assembled tapered ZnO nanorods via a template free one-pot synthesis: significant cathodoluminescence and field emission properties - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Patil, Kashinath R.; Koinkar, Pankaj M.; More, Mahendra A.; Murakami, Ri-ichi (Journal of Materials Chemistry, 2012)
The present investigation explores the controlled architecture of a CeO2-ZnO nanocomposite via a template-free, low temperature, facile single step solvothermal approach. This complex architecture depicts cubic single crystalline CeO2 nanoparticles (size similar to 15 nm) grown on the edges of tapered ZnO nanorods with definite orientations and alignments. The formation of wurtzite ZnO, cubic CeO2 and the coexistence of Ce3+ and Ce4+ on the surface of the CeO2-ZnO nanocomposites are confirmed using various characterization tools. The finding of such unique nanostructures by a facile method is exemplified by a plausible growth mechanism. Surprisingly, the aqueous mediated ultrasonication reaction conferred the formation of crystalline ZnO nanotubes of diameter similar to 50 nm. Spatially resolved cathodoluminescence spectra are obtained by linearly scanning an individual CeO2-ZnO nanorod along its length, which reveals the size-dependent surface effects. Interestingly, such hybrid CeO2-ZnO nanoarchitecture is observed to exhibit enhanced field emission properties, demonstrating better current stability as compared to other ZnO nanostructures. This is attributed mainly to strong surface interactions between the Ce-ionic species and the ZnO nanorods. Herein, a soft-chemical approach is used for the first time to architect a binary oxide nanostructure, which is otherwise accomplished using high temperature techniques, as reported elsewhere. Also, the present work not only gives insight into understanding the hierarchical growth behaviour of the CeO2-ZnO nanocomposite in a solution phase synthetic system, but also provides an efficient route to enhance the field emission performance of ZnO nanostructures, which could be extended to other potential applications, such as chemical sensors, optoelectronic devices and photocatalysts.

Vertical arrays of SiNWs-ZnO nanostructures as high performance electron field emitters - Devarapalli, Rami Reddy; Shinde, Deodatta R.; Barka-Bouaifel, Fatiha; Yenchalwar, Sandeep G.; Boukherroub, Rabah; More, Mahendra A.; Shalke, Manjusha V. (Journal of Materials Chemistry, 2012)
Multicomponent hybrid materials of nanostructured building blocks are essential for the development of complex devices and advanced applications due to their role as either functional or interconnecting elements. This study introduces a simple and cost effective strategy for the synthesis of vertical arrays of silicon nanowires and ZnO nanostructures (nanorod and multipod structures). Formation of vertical nanostructured arrays is confirmed by SEM and HRTEM imaging as well as XRD and Raman measurements. We have investigated field emission properties of the as-synthesized vertical nanostructured arrays. Our results show that these SiNWs-ZnO nanostructures are highly efficient and stable field emitters.

Controlled synthesis of aligned Bi2S3 nanowires, sharp apex nanowires and nanobelts with its morphology dependent field emission investigations - Warule, Sambhaji S.; Chaudhari, Nilima S.; Kale, Bharat B.; Pandiraj, S.; Khare, Ruchita T.; More, Mahendra A. (Crystengcomm, 2013)
Well-aligned ultra-long Bi2S3 nanowire arrays with three kinds of apex morphology - abruptly sharpened apex, thin belt and flat - have been systematically fabricated on tungsten (W) foil by a facile hydrothermal method. The structural and morphological studies reveal formation of distinct tip morphologies, possessing high aspect ratio, single crystalline nature and growth along the orthorhombic [001] axis. A plausible growth mechanism has been proposed on the basis of observed experimental results. The field emission properties of Bi2S3 nanowires and sharp apex Bi2S3 nanowires are investigated. From the field emission studies, the values of the turn-on field, required to draw emission current density of similar to 0.1 mu A cm(-2), are observed to be similar to 2.01 and 1.21 V mu m(-1) for nanowires and sharp apex nanowires, respectively. Furthermore, ultra-long Bi2S3 nanowires are also grown on the W microtip (brush-like) from which very high emission current density similar to 11 mA cm(-2) has been drawn. These results are helpful for the design, fabrication and optimization of integrated field emitters using 1D nanostructures as cold cathode material.

Enhanced field-emission behavior of layered MoS2 sheets - Kashid, Ranjit V.; Late, Dattatray J.; Chou, Stanley S.; Huang, Yi-Kai; De, Mrinmoy; Joag, Dilip S.; More, Mahendra A.; Dravid, Vinayak P. (Small, 2013)
Field emission studies are reported for the first time on layered MoS2 sheets at the base pressure of approximate to 1 x 10(-8) mbar. The turn-on field required to draw a field emission current density of 10 A/cm(2) is found to be 3.5 V/m for MoS2 sheets. The turn-on values are found to be significantly lower than the reported MoS2 nanoflowers, graphene, and carbon nanotube-based field emitters due to the high field enhancement factor (approximate to 1138) associated with nanometric sharp edges of MoS2 sheet emitter surface. The emission current-time plots show good stability over a period of 3 h. Owing to the low turn-on field and planar (sheetlike) structure, the MoS2 could be utilized for future vacuum microelectronics/nanoelectronic and flat panel display applications.

High efficiency electron field emission from protruded graphene oxide nanosheets supported on sharp silicon nanowires - Devarapalli, Rami Reddy; Kashid, Ranjit V.; Deshmukh, Ashvini B.; Sharma, Ponchami; Das, Manash R.; More, Mahendra A.; Shelke, Manjusha V. (Journal of Materials Chemistry C, 2013)
Graphene oxide (GO) potentially has applications in vacuum microelectronic devices for realization of field emission displays. Graphene and its derivatives are expected to be efficient field emitters due to their unique electrical properties. However, the flat sheet structure of graphene or GO allows electron field emission only from the edges of graphene and GO nanosheets. In order to extract maximum field emission current density at lower applied voltage from the GO nanosheets, we supported and stretched them on sharp tips of silicon nanowires (SiNWs). Highly efficient and stable field emission with low turn-on field was observed for these SiNW-GO heterostructures. The sharp protrusions created by stretching of the GO nanosheets on SiNWs locally enhance the electric field and thus enhance the field emission characteristics. The dominant use of silicon in electronic devices makes this approach robust for the development of field emission devices using graphene based field emitters.

Superior field emission properties of layered WS2-RGO nanocomposites - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Scientific Reports, 2013)
We report here the field emission studies of a layered WS2-RGO composite at the base pressure of similar to 1 x 10(-8) mbar. The turn on field required to draw a field emission current density of 1 mu A/cm(2) is found to be 3.5, 2.3 and 2 V/mu m for WS2, RGO and the WS2-RGO composite respectively. The enhanced field emission behavior observed for the WS2-RGO nanocomposite is attributed to a high field enhancement factor of 2978, which is associated with the surface protrusions of the single-to-few layer thick sheets of the nanocomposite. The highest current density of similar to 800 mu A/cm(2) is drawn at an applied field of 4.1 V/mu m from a few layers of the WS2-RGO nanocomposite. Furthermore, first-principles density functional calculations suggest that the enhanced field emission may also be due to an overalp of the electronic structures of WS2 and RGO, where graphene-like states are dumped in the region of the WS2 fundamental gap.

CdS nanowires: ultra-long growth and enhanced field emission properties - Chavan, Padmakar G.; Kashid, Ranjit V.; Badhade, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Vaccum, 2014)
Here, we report the synthesis of ultra-long CdS nanowires with aspect ratio similar to 8 x 10(4) by simple route of thermal evaporation technique. A change in the vertical arrangement of quartz boats leads in to the synthesis of ultra-long CdS nanovvires via high degree of condensation. This technique is seen to be cost effective and easy. The growth of the nanowires is found to be increased very rapidly from few micrometers to few millimeters. The possible reason for the growth of the ultra-long CdS nanowires is discussed in detail. The turn-on field defined for the current density of similar to 0.1 mu A/cm(2) has been found to be similar to 1.4, 1.45, 1 and 0.17 V/mu m for specimen A, B, C and D (specimens A-D, synthesized by variation in synthesis parameters) respectively. The turn-on field of the specimen D (similar to 0.17 V/mu m) is found to be quite superior than the value reported for other CdS nanoforms which is very remarkable. Simple way of bulk fabrication leads to the low turn-on value which indicates a possible use of the present emitter in the micro/nanoelectronics devices. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Current stability; field emission; synthesis

Enhanced field emission properties of doped graphene nanosheets with layered SnS2 - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Applied Physics Letters, 2014)
We report here our experimental investigations on p-doped graphene using tin sulfide (SnS2), which shows enhanced field emission properties. The turn on field required to draw an emission current density of 1 mu A/cm(2) is significantly low (almost half the value) for the SnS2/reduced graphene oxide (RGO) nanocomposite (2.65 V/mu m) compared to pristine SnS2 (4.8 V/mu m) nanosheets. The field enhancement factor beta (similar to 3200 for the SnS2 and similar to 3700 for SnS2/RGO composite) was calculated from Fowler-Nordheim (F-N) plots, which indicates that the emission is from the nanometric geometry of the emitter. The field emission current versus time plot shows overall good emission stability for the SnS2/RGO emitter. The magnitude of work function of SnS2 and a SnS2/graphene composite has been calculated from first principles density functional theory (DFT) and is found to be 6.89 eV and 5.42 eV, respectively. The DFT calculations clearly reveal that the enhanced field emission properties of SnS2/RGO are due to a substantial lowering of the work function of SnS2 when supported by graphene, which is in response to p-type doping of graphene. (C) 2014 AIP Publishing LLC.

Enhancement in the field emission behavior of graphene in N-2/O-2 high vacuum ambience - Suryawanshi, S. R.; Kolhe, Pankaj S.; Gavhane, D. S.; Patil, S. S.; Chavan, P. G.; More, Mahendra A.; Late, Dattatray J. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Herein we report, pressure dependent field emission (FE) behaviour of a few-layer graphene emitter. Gas dependent FE properties have been investigated in ultra high vacuum (UHV), as well as in N-2 and O-2 ambience at base pressure similar to 1x10(-6) torr. Interestingly, the graphene emitter when operated in N-2/O-2 ambience exhibits lower turn-on field and higher emission current density, as compared to the UHV conditions. The emission current stability investigated at preset value of similar to 1 mu A over the period of more than 2 hrs is found better in the N2 ambience and is characterized by fewer fluctuations, in contrast to the behaviour in the O-2 ambience. The observed enhanced electron emission behavior in N-2/O-2 ambience is attributed to modulation of the work function of graphene emitter.
Keywords: graphene; Pressure Dependent Field Emission

Field emission properties of ZnO nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Chakravarty, Disha; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2014)
{Electron emission properties of electrodeposited ZnO nanosheet arrays grown on Indium tin oxide coated glass substrates have been studied. Influence of oxygen vacancies on electronic structures and field emission properties of ZnO nanosheets are investigated using density functional theory. The oxygen vacancies produce unshared d electrons which form an impurity energy state; this causes shifting of Fermi level towards the vacuum, and so the barrier energy for electron extraction reduces. The ZnO nanosheet arrays exhibit a low turn-on field of 2.4 V/mu m at 0.1 mu A/cm(2) and current density of 50.1 mu A/cm(2) at an applied field of 6.4 V/mu m with field enhancement factor

Metallic few-layer flowerlike VS2 nanosheets as field emitters - Rout, Chandra Sekhar; Khare, Ruchita T.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Lanzillo, Nicholas A.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2014)
We report first-principles DFT calculations of the single-layer VS2 work function, the experimental synthesis of flower-like few-layer-thick VS2 nanosheets by a simple one-step hydrothermal method, and the investigation of their field emission properties. The turn-on field required to draw emission current densities of 1 and 10 mu A/cm(2) were 4 and 5.01 V/mu m, respectively. The observed turn-on field values are attributed to the high field enhancement factor (ca. 2500), which is due to presence of sharp protrusions in the VS2 nanosheets. Furthermore, the field-emission current stability of the VS2 emitter shows stable behavior over a period of 12 h. Further, DFT calculations show that the work function (f) of the single-layer VS2 emitter is 6.01 eV.
Keywords: Density functional calculations; field emission; Layered compounds; Nanostructures; Sulfur; Vanadium

Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
Keywords: Current stability; field emission; Nanobelts; Photoswitching

Pulsed laser-deposited MoS2 thin films on W and Si: field emission and photoresponse studies - Late, Dattatray J.; Shaikh, Parvez A.; Khare, Ruchita T.; Kashid, Ranjit V.; Chaudhary, Minakshi V.; More, Mahendra A.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2014)
We report field electron emission investigations on pulsed laser-deposited molybdenum disulfide (MoS2) thin films on W-tip and Si substrates. In both cases, under the chosen growth conditions, the dry process of pulsed laser deposition (PLD) is seen to render a dense nanostructured morphology of MoS2, which is important for local electric field enhancement in field emission application. In the case of the MoS2 film on silicon (Si), the turn-on field required to draw an emission current density of 10 mu A/cm(2) is found to be 2.8 V/mu m. Interestingly, the MoS2 film on a tungsten (W) tip emitter delivers a large emission current density of similar to 30 mA/cm(2) at a relatively lower applied voltage of similar to 3.8 kV. Thus, the PLD-MoS2 can be utilized for various field emission-based applications. We also report our results of photodiode-like behavior in (n- and p- type) Si/PLDMoS2 heterostructures. Finally we show that MoS2 films deposited on flexible kapton substrate show a good photoresponse and recovery. Our investigations thus hold great promise for the development of PLD MoS2 films in application domains such as field emitters and heterostructures for novel nanoelectronic devices.
Keywords: field emission; MoS2; photodiode heterostructures; pulsed laser deposition; thin film

Vapor-liquid-solid growth of one-dimensional tin sulfide (sns) nanostructures with promising field emission behavior - Suryawanshi, Sachin R.; Warule, Sambhaji S.; Patil, Sandip S.; Patil, Kashinath R.; More, Mahendra A. (ACS Applied Materials & Interfaces, 2014)
Single-crystalline ultralong tin sulfide (SnS) nanowires has been grown by a thermal evaporation technique under optimized conditions on gold-coated silicon substrates, and for the first time, field emission investigations on the SnS nanowires at the base pressure of 1 X 10(-8) mbar are reported. It has been revealed that the surface morphology of the as-synthesized SnS nanostructures is significantly influenced by the deposition temperature and duration. Structural and morphological analyses of as-synthesized SnS nanostructures have been carried out using X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). To understand the optical and electronic properties of as-synthesized SnS nanowires, ultraviolet-visible (UV-vis), photo-luminescence (PL), and X-ray photoelectron spectroscopy (XPS) studies were carried out. The SEM and TEM measurements reveal the formation of ultralong SnS nanowires, with an average diameter of 80 nm. A plausible explanation on the vapor-solid-liquid (VLS) growth mechanism based on the experimental results and reported literature has been presented. Furthermore, the field emission characteristics of the SnS nanowires are found to be superior to the other metal chalcogenide nanostructures. The synthesized SnS nanowire emitter delivers a high current density of similar to 2.5 mA/cm(2) at an applied electric field of similar to 4.55 V/mu m. The emission current stability over a period of 6 h is observed to be good. The observed results demonstrate the potential of the SnS nanowire emitter as an electron source for practical applications in vacuum nano/microelectronic devices.
Keywords: Electron emission; ID nanostructure; SnS nanowires; thermal evaporation; vapor-liquid-solid (VLS) growth

3D Hetero-architecture of GdB6 nanoparticles on lessened cubic Cu2O nanowires: enhanced field emission behaviour - Suryawanshi, Sachin R.; Singh, Anil K.; Deo, Meenal S.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (CrystEngComm, 2015)
The field emission properties (FE) of a heteroarchitecture comprised of gadolinium hexaboride nanoparticles uniformly decorated over Cu2O nanoneedles (GdB6/Cu2O) have been investigated at the base pressure of similar to 1 x 10(-8) mbar. Under the optimized pulsed laser deposition (PLD), a well-adhered coating of GdB6 nanoparticles on chemically synthesized cuprous oxide (Cu2O) nanoneedles has been obtained. A plausible growth mechanism of the hierarchical assembly of GdB6 nanoparticles on the Cu2O nanoneedles is explained on the basis of structural analysis carried out using SEM and TEM. A low turn-on field of similar to 2.3 V mu m(-1) (to draw an emission current density similar to 1 mu A cm(-2)) is observed along with stable emission current at the preset value of similar to 2 mu A over 4 h. The enhanced emission behaviour of the GdB6/Cu2O heteroarchitecture, in contrast to the pristine Cu2O nanoneedles, is attributed to its high aspect ratio and low work function. The observed FE results demonstrate GdB6/Cu2O heteroarchitecture as a potential candidate for application in various vacuum nano/microelectronic devices.

Black phosphorous nanosheets: prospective field emitter - Late, Dattatray J.; Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A. (2015 28th International Vacuum Nanoelectronics Conference (IVNC), 2015)
We report for the first time field electron emission investigations on few layered black phosphorous nanosheets emitter's synthesized using chemical method with thickness similar to 2-5 nm. The turn-on electric field required to draw an emission current density of similar to 10 mu A/cm(2) was found to be similar to 4.2 V/mu m. Furthermore, a few layer black phosphorous nanosheets emitter deliver an large emission current density of similar to 170 mu A/cm(2) at an applied field of similar to 7.5 V/mu m. The emission current versus time plot measured at the preset current values of similar to 5 mu A shows field emission current fluctuations within +/- 10% of the average value indicating the well stable nature of black phosphorous field emitter. Thus, the two dimensional black phosphorous nanosheets synthesized using simple electrochemical exfoliation method can be realized and utilized for the next generation micro/nanoelectronics and flat panel field emission based display applications.

Decoration of CdS nanoparticles on 3D self-assembled ZnO nanorods: a single-step process with enhanced field emission behaviour - Warule, Sambhaji S.; Chaudhari, Nilima S.; Shisode, Raju T.; Desa, Keith V.; Kale, Bharat B.; More, Mahendra A. (CrystEngComm, 2015)
A well-defined CdS-ZnO heteroarchitecture has been synthesized via a facile single-step hydrothermal approach. The morphological and structural studies reveal the formation of 3D nano-architectures, in which self-assembled ZnO nanorods (diameter similar to 50 nm) are well decorated with single crystalline CdS nanoparticles (size similar to 10 nm). The CdS-ZnO heteroarchitecture exhibits a remarkable change in the optical absorption due to the surface modification of ZnO nanorods by CdS. Surprisingly, under identical reaction conditions, the global ZnS nanoparticles are selectively grown at the apex of ZnO nanorods on the Zn substrate. Furthermore, a plausible growth mechanism has been presented on the basis of experimental results. Interestingly, the CdS-ZnO heteroarchitecture shows enhanced field emission properties such as low turn-on field, high emission current density and better current stability in comparison to other ZnO-based nanostructures. The present CdS-ZnO heteroarchitecture could be extended to other potential applications, such as chemical sensors, photodetectors, optoelectronic devices, and photocatalysts.

Electrochemically exfoliated black phosphorus nanosheets - prospective field emitters - Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
Herein we report field emission (FE) investigations on an electrochemically exfoliated few-layered black phosphorus nanosheet emitter at a base pressure of approximately 1x10(-8) mbar. The turn-on electric field required to draw an emission current density of approximately 10 A/cm(2) is found to be about 4.2 V/m. Furthermore, few-layered black phosphorus nanosheet emitters deliver an emission current density of about 170 A/cm(2) at an applied field of about 7.5 V/m. The emission current vs. time plot measured at preset current values of about 5 A shows emission current fluctuations within +/- 10% of the average value, indicating the highly stable nature of the black phosphorus field emitter. Thus, the 2D black phosphorus nanosheets synthesized using the simple electrochemical exfoliation method can be utilized for micro/nanoelectronics and flat panel FE display applications.
Keywords: field emission; Layered compounds; Nanostructures; Phosphorus

Enhanced electron field emission from NiCo2O4 nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Materials Research Express, 2015)
Electron emission properties of electrodeposited spinel NiCo2O4 nanosheet arrays grown on Ni foam have been studied. The work function of NiCo2O4 was calculated by density functional theory using the plane-wave basis set and used to estimate the field enhancement factor. The NiCo2O4 nanosheet arrays exhibited a low turn-on field of 1.86 V mu m(-1) at 1 mu A cm(-2) and current density of 686 mu A cm(-2) at 3.2 V mu m(-1), with field enhancement factor beta = 1460 and good field emission current stability. The field emission properties of the NiCo2O4 nanosheet arrays showed enhanced performance compared to chemically prepared NiCo2O4 nanosheets. Hence, the nanosheet arrays have great potential as robust high performance vertical structure electron emitters for future flat panel displays and vacuum electronic device applications.
Keywords: Density functional theory; field emission; nanosheets; NiCo2O4; spinel

Enhanced field emission of plasma treated multilayer graphene - Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Physics Letters, 2015)
Electron emission properties of multilayer graphene (MLG) prepared by a facile exfoliation technique have been studied. Effect of CO2 Ar, N-2, plasma treatment was studied using Raman spectroscopy and investigated for field emission based application. The CO2 plasma treated multilayer graphene shows an enhanced field emission behavior with a low turn on field of 0.18 V/mu m and high emission current density of 1.89 mA/cm(2) at an applied field of 0.35 V/mu m. Further the plasma treated MLG exhibits excellent current stability at a lower and higher emission current value. (C) 2015 AIP Publishing LLC.

Facile synthesis of Ag nanowire-rGO composites and their promising field emission performance - Samantara, Aneeya K.; Mishra, Dillip Kumar; Suryawanshi, Sachin R.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Jena, Bikash Kumar; Rout, Chandra Sekhar (RSC Advances, 2015)
Crystalline, ultra long silver nanowires (Ag NWs), few-layered rGO (reduced graphene oxide) and their rGO-Ag NW nanocomposite have been synthesized using a polyol reflux technique under optimized experimental conditions. The field emission performance of the rGO-Ag NW nanocomposite, rGO and Ag NW emitters was investigated. The turn on field required to draw an emission current density of similar to 1 mA cm(-2) was found to be similar to 5.00, 3.92 and 2.40 V mu m(-1) for the Ag NW, rGO and rGO-Ag NW nanocomposite emitters, respectively. The combined contribution of the sharp edges of the thin graphene sheets and high aspect ratio of the Ag nanowires, and their synergetic effect in the rGO-Ag NW nanocomposite, are responsible for the enhanced field emission behavior. First-principles density functional calculations show that the enhanced field emission may also be due to the overlapping of the electronic structures of the Ag NWs and rGO nanosheets.

Field emission properties of spinel ZnCo2O4 microflowers - Ratha, Satyajit; Khare, Ruchita T.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2015)
ZnCo2O4 microflowers were synthesized by a simple low temperature hydrothermal route. A single three-dimensional microflower consists of hundreds of self-assembled petals, with a thickness of several nanometers. These microflowers have exceptionally thin edges with a few petal layers. The ZnCo2O4 microflowers appeared to be stable and good field emitters.

Graphene nanoribbons as prospective field emitter - Khare, Ruchita T.; Shinde, Dhanraj B.; Bansode, Sanjeewani; More, Mahendra A.; Majumder, Mainak; Pillai, Vijayamohanan K.; Late, Dattatray J. (Applied Physics Letters, 2015)
Field emission characteristics of graphene nanoribbons (GNRs) synthesized by unzipping of multiwall carbon nanotubes using a facile hydrothermal route have been investigated at a base pressure of 1 x 10(-8) mbar. The values of turn-on field, required to draw an emission current densities of 1 and 10 mu A/cm(2), are found to be 2.8 and 5.8 V/mu m, respectively, and a maximum emission current density of 500 mu A/cm(2) has been drawn at an applied field of 9.8 V/mu m. The emission current stability of the GNRs emitter was studied at preset values of 1 and 10 mu A over a period of 3 h, and is found to be excellent. The field emission results demonstrated herein suggest that GNRs based field emitters can open up many opportunities for their potential utilization as large area field emitters in various vacuum micro-nanoelectronic devices such as flexible field emission displays, portable X-ray, and microwave tubes. (C) 2015 AIP Publishing LLC.

Multifunctional polyaniline-tin oxide (PANI-SnO2) nanocomposite: synthesis, electrochemical, and field emission investigations - Patil, Sandip S.; Harpale, Kashmira V.; Koiry, Shankar P.; Patil, Kashinath R.; Aswal, Dinesh K.; More, Mahendra A. (Journal of Applied Polymer Science, 2015)
Synthesis of PANI-SnO2 nanocomposite has been performed using a simple two step chemical oxidative polymerization route. The structural, morphological and chemical properties of the as-synthesized PANI-SnO2 nanocomposite have been revealed by various characterization techniques such as SEM, TEM, XRD, FTIR, and XPS. Interestingly the as-synthesized PANI-SnO2 nanocomposite exhibits supercapacitance value of 721 F g(-1) with energy density 64 Wh kg(-1), which is noticed to be higher than that of pristine SnO2 and PANI nanostructures. Furthermore, the galvanostatic charge-discharge characteristics revealed pseudocapacitive nature of the PANI-SnO2 nanocomposite. The estimated values of charge transfer resistance and series resistance estimated from the Nyquist plot are found to be lower. Along with the supercapacitive nature, PANI-SnO2 nanocomposite showed promising field emission behavior. The threshold field, required to draw emission current density of 1 A/cm(2), is observed to be 0.90 V/m and emission current density of 1.2 mA/cm(2) has been drawn at applied field of approximate to 2.6 V/m. The emission current stability investigated at preset values of 0.02 and 0.1 mA/cm(2) is observed to be fairly stable over duration of more than 3 h. The enhanced supercapacitance values, as well as, the promising field emission characteristics are attributed to the synergic effect of SnO2 nanoparticles and PANI nanotubes. (c) 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41401.
Keywords: conducting polymers; Electrochemistry; nanostructured polymers; surfaces and interfaces

One-pot thermal evaporation synthesis of CdS-RGO hetrostructure and its field emission study - Bansode, Sanjeewani R.; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J. (2015 28TH International Vacuum Nanoelectronics Conference (IVNC), 2015)
CdS-RGO heterostructure was synthesized by thermal evaporation method. The as-synthesized CdS-RGO heterostructure was characterized using X-ray Diffraction, SEM, and EADX, before field emission (FE) studies. The FE characteristics of a planar emitter made up of as-synthesized CdS-RGO heterostructures were measured at the base pressure 1x10(-8) mbar. The synthesized CdS-RGO heterostructure emitter is found to deliver a current density similar to 70 mu A/cm(2) at an applied electric field of similar to 4.7 V/mu m. Moreover, the nanocomposite shows excellent emission stability without significant current degradation making CdS-RGO heterostructure as a promising electron source for practical applications in various vacuum nano-microelectronic devices.

Pt-nanoparticle functionalized carbon nano-onions for ultra-high energy supercapacitors and enhanced field emission behaviour - Suryawanshi, Sachin R.; Kaware, Vaibhav; Chakravarty, Disha; Walke, Pravin S.; More, Mahendra A.; Joshi, Kavita; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2015)
In the present work, we have investigated the charge storage capacitive response and field emission behaviour of platinum (Pt) nanoparticles decorated on carbon nano onions (CNOs) and compared them with those of pristine carbon nano onions. The specific capacitance observed for Pt-CNOs is 342.5 F g(-1), about six times higher than that of pristine CNOs, at a scan rate of 100 mV s(-1). The decoration with Pt nanoparticles, without any binder or polymer separator on the CNO, leading to enhanced supercapacitance is due to easy accessibility of Na2SO4 electrolyte in the active material. The Density Functional Theory (DFT) calculations of these systems reveal enhancement in the Density of States (DOS) near the Fermi energy (E-F) on account of platinum decoration on the CNOs. Furthermore, the field emission current density of similar to 0.63 mA cm(-2) has been achieved from the Pt-CNOs emitter at an applied electric field of similar to 4.5 V mu m(-1) and from the pristine CNOs sample current density of similar to 0.4 mA cm(-2) has been achieved at an applied electric field of similar to 6.6 V mu m(-1). The observed enhanced field emission behavior has been attributed to the improved electrical conductivity and increased emitting sites of the Pt-CNO emitter. The field emission current stability of the Pt-CNO emitter over a longer duration is found to be good. The observed results imply multifunctional potential of Pt-CNOs, as supercapacitor material in various next generation hybrid energy storage devices, and field emitters for next generation vacuum nano/microelectronic devices.

Spectral analysis of the emission current noise exhibited by few layer WS2 nanosheets emitter - Suryawanshi, Sachin R.; Kolhe, Pankaj S.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Ultramicroscopy, 2015)
Spectral analysis of the field emission (FE) current fluctuations has been carried out at the base pressure similar to 1 x 10(-8) mbar. The emission current stability investigated at preset value of 2 mu A is characterized by `step like fluctuation. The spectral analysis performed on a FFT (Fast Fourier Transform) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha as similar to 1.05. The estimated value of alpha implies that the current fluctuations are mainly due the various processes occurring on atomic scale like adsorption, migration, and/or desorption of the residual gas species on the emitter surface. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Current fluctuations; field emission; Noise; WS2 nanosheets

Stable field emission from layered MoS2 nanosheets in high vacuum and observation of 1/f noise - Kashid, Ranjit V.; Joag, Pracheetee D.; Thripuranthaka, M.; Rout, Chandra S.; Late, Dattatray J.; More, Mahendra A. (Nanomaterials and Nanotechnology, 2015)
Field emission and current noise of hydrothermally synthesized MoS2 nanosheets are investigated in ultra-high-vacuum and industrially suited high-vacuum conditions. The study reveals that the emission turn-on field is pressure dependent. Moreover, the MoS2 nanosheets exhibit more stable field-electron emission in high-vacuum than in ultra-high-vacuum conditions. The investigations on field-emission current fluctuations show features of 1/f-type noise in ultra-high-vacuum and high-vacuum conditions, attributed to adsorption and desorption processes. The post-field-emission results indicate the MoS2 nanosheets are a robust field emitter in high-vacuum conditions.
Keywords: Electron emission; layered materials; MoS2; Noise measurement; Raman spectroscopy

Synthesis of GdB6 nanostructures using nanosecond (Nd: YAG) laser: field emission investigation - Suryawanshi, S. R.; Late, Dattatray J.; More, Mahendra A.; Singh, Anil K.; Sinha, S. (2015 28th International Vacuum Nanoelectronics Conference (IVNC), 2015)
We herein report field emission characteristics of GdB6 nanostructures grown directly on a pellet via laser processing (laser fluence similar to 6 J/cm(2)). The laser processed GdB6 pellet was characterized by X-ray diffraction, which revealed no change in phase upon laser processing. The values of the turn-on field required to draw emission current density of 1 mu A/cm(2) is found to be similar to 2.95 V/mu m, for the laser processed GdB6 emitter. Furthermore, the Fowler-Nordheim (F-N) plot exhibits non-linear behavior over the entire range of applied field and the field enhancement factor (beta) calculated from slope of the F-N plot (low field region) was found to be similar to 543. The emission current stability over a period of 3h was observed to be fairly good. The observed results demonstrate that laser processing can be efficiently used to make GdB6 nanostructure emitter having potential for practical applications.

Transition metal di-chalcogenides and their nanocomposite prospective field emitters - Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J. (2015 28TH International Vacuum Nanoelectronics Conference (IVNC), 2015)
Layered structured transition metal di-chalcogenides has attracted researchers as a substitute of graphene and its forms for various applications. In an attempt to explore field emission properties of these graphene analogues, synthesis and field emission behaviour of a few layered transition metal di-chalcogenides (TMDs) VS2, MoS2, MoO3 have been investigated at a base pressure of 1x 10(-8) mbar. Furthermore, to improve the field emission properties, composites with RGO and respective oxides were synthesized and compared with the pristine ones. The TMDs and their composites is synthesized employing hydrothermal synthesis route. The preliminary results show that these TMD's and their composites, when synthesized in a controlled manner, can serve as potential field emitters for future field emission based devices.

Ultra-thin V2O5 nanosheet based humidity sensor, photodetector and its enhanced field emission properties - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2015)
We report the synthesis of V2O5 nanosheets by a simple hydrothermal method. The as synthesized V2O5 nanosheets were characterized by Raman spectroscopy, Field Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM) and UV-Vis spectroscopy. The humidity sensing behaviors were investigated in the range of 11-97% relative humidity (RH) at room temperature. The maximum sensitivity of 45.3%, response time of similar to 4 min and recovery time of similar to 5 min were observed for the V2O5 nanosheet based sensor. We also demonstrated the V2O5 nanosheets as an ultra-violet photodetector with a sensing response time of similar to 65 s and recovery time of similar to 75 s with a maximum photoresponsivity of similar to 6.2%. Further, we have also carried out field emission (FE) investigations of V2O5 nanosheets under a planar ``Diode'' assembly in an ultrahigh vacuum (UHV) chamber at a base pressure of similar to 1 x 10(-8) mbar. The turn on fields required to draw field emission current densities of 1 mu A cm(-2) and 10 mu A cm(-2) are found to be 1.15 V mu m(-1) and 1.72 V mu m(-1), respectively. We achieved a maximum field emission current density of 1.532 mA cm(-2) at an applied electric field of 3.2 V mu m(-1). The field enhancement factors calculated from the slope of the Fowler-Nordheim (F-N) plot are found to be 8530 and 3530 at low field and high field regions, respectively. Our results open up several avenues towards the successful utilization of V2O5 nanosheets and other metal oxide nanosheets for various nanoelectronics device applications including sensors, photodetector and flat panel displays.

Vapour-liquid-solid growth of one-dimensional In2Se3 nanostructures and their promising field emission behaviour - Suryawanshi, Sachin R.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2015)
Single crystalline ultra long In2Se3 nanowires have been grown by employing a single step facile thermal evaporation route under optimized conditions on Au/Si wafers, and morphology dependent field emission investigations on the In2Se3 nanostructure at the base pressure -1 x 10(-8) mbar are explored. In addition, structural and morphological analysis of as-synthesized In2Se3 nanostructures has been carried out using XRD, SEM and TEM. A plausible explanation of the vapor-solid-liquid (VLS) growth mechanism based on the experimental results and reported literature has been presented. Furthermore, field emission measurements demonstrate remarkably enhanced emission behaviour, which is explained on the basis of the field enhancement factor and aspect ratio of the nanostructures. The synthesized In25e3 nanowire emitter delivers a very high current density of -1.2 mA cm(-2) at an applied electric field of -6.33 cm(-1). The present results demonstrate In2Se3 as an important candidate for potential applications in nano/micro-electronic devices.

Architecture of 2D MoS2 nanosheets and 3D CdMoS4 marigold flowers: consequence of annealing on field emission performance - Kadam, Sunil R.; Suryawanshi, Sachin R.; Panmand, Rajendra P.; Mate, Vivek R.; More, Mahendra A.; Late, Dattatray J.; Kale, Bharat B. (Microporous and Mesoporous Materials, 2016)
Herein, we report the field electron emission investigations on template free solvothermally synthesized layered MoS2 nanosheets as well as novel phase of CdMoS4 nanoflowers at the base pressure of similar to 1 x 10(-8) mbar. The turn-on field, threshold field and maximum emission current densities for both MoS2 and CdMoS4 are strongly influenced by thermal annealing in inert atmosphere. The turn on field, required to draw emission current density of 1 mu A/cm(2) is found to be 5.8 and 3.2 V/mu m for pristine and annealed MoS2 at 400 degrees C. In case of as prepared and annealed CdMoS4 sample the turn on field values are found to be similar to 6.2 and 5.0 V/mu m, respectively. The emission current versus time (I-t) plot measured at the preset current values of similar to 1 mu A for pristine and annealed sample indicates stable operation of the emitter. The emission current fluctuations for annealed sample are observed to be less as compared with the pristine sample due to conditioning of the emitter, thereby showing highly stable nature of emitter. Thus, the present result demonstrates the potential of annealed MoS2 nanosheets and CdMoS4 nanoflowers as an emerging materials for micro/nanoelectronics and flat panel field emission display applications. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: field emission; MoS2 and CdMoS4; Nanoflowers; nanosheets

Enhanced field emission behavior of layered MoSe2 - Suryawanshi, Sachin R.; Pawbake, Amit S.; Pawar, Mahendra S.; Jadkar, Sandesh R.; More, Mahendra A.; Late, Dattatray J. (Materials Research Express, 2016)
Herein, we report one step facile chemical vapor deposition method for synthesis of single-layer MoSe2 nanosheets with average lateral dimension similar to 60 mu m on 300 nm SiO2/Si and n-type silicon substrates and field emission investigation of MoSe2/Si at the base pressure of similar to 1 x 10(-8) mbar. The morphological and structural analyses of the as-deposited single-layer MoSe2 nanosheets were carried out using an optical microscopy, Raman spectroscopy and atomic force microscopy. Furthermore, the values of turn-on and threshold fields required to extract an emission current densities of 1 and 10 mu A cm(-2), are found to be similar to 1.9 and similar to 2.3 V mu m(-1), respectively. Interestingly, the MoSe2 nanosheet emitter delivers maximum field emission current density of similar to 1.5 mA cm(-2) at a relatively lower applied electric field of similar to 3.9 V mu m(-1). The long term operational current stability recorded at the preset values of 35 mu A over 3 hr duration and is found to be very good. The observed results demonstrates that the layered MoSe2 nanosheet based field emitter can open up many opportunities for their potential application as an electron source in flat panel display, transmission electron microscope, and x-ray generation. Thus, the facile one step synthesis approach and robust nature of single-layer MoSe2 nanosheets emitter can provide prospects for the future development of practical electron sources.
Keywords: atomically thin nanosheets; chemical vapor deposition; field emission; layered MoSe2

Exfoliated 2D black phosphorus nanosheets: field emission studies - Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (Journal of Vacuum Science & Technology B, 2016)
A few layer black phosphorus (BP) nanosheets are obtained by micromechanical cleavage from a bulk BP crystal. In a typical exfoliation procedure, a layer of BP is peeled off from bulk crystal with the help of Scotch tape and transferred onto SiO2/Si and pristine Si substrates. The morphological and structural analyses of the samples were carried out using an optical microscopy, a transmission electron microscopy, and a Raman spectroscopy. Field emission investigations on a few layered BP nanosheets on Si substrate were carried out at the base pressure of 1 x 10(-8) mbar. The turn-on value, corresponding to emission current density of similar to 1 mu A/cm(2), is found to be similar to 5.1V/mu m for BP nanosheets/Si emitter and high field enhancement factor (beta) similar to 1164, attributed to atomically thin/sharp edges of the BP nanosheets. The emission current shows good stability at a preset value of similar to 5 mu A over a period of more than 8 h. The present results demonstrate the potential of the mechanically exfoliated BP nanosheets/Si field emitter for the development of practical electron sources. (C) 2016 American Vacuum Society.

Facile approach towards fabrication of GdB6-ZnO heteroarchitecture as high currentdensity cold cathode - Suryawanshi, Sachin R.; Mistari, Chetan D.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Chemistryselect, 2016)
Three dimensional (3D) GdB6-ZnO heteroarchitecture comprised of thin coating of GdB6 on self aligned ZnO urchins with pointed apex has been synthesized employing optimized Pulsed Laser Deposition (PLD) technique. The self aligned ZnO urchins on Zn substrate were obtained using hydrothermal route. The as-synthesized GdB6-ZnO heteroarchitecture was characterized using XRD, SEM, TEM XPS, and UPS in order to reveal its structural, morphological, chemical, and electronic properties. Interestingly, the GdB6-ZnO heteroarchitecture exhibits superior field emission (FE) behviour in contrast to the pristine ZnO urchins envisaged by extraction of very high emission current density of similar to 4.6 mA/cm(2) at an applied field of similar to 4.5 V/mm, against similar to 1.5 mA/cm(2) at an applied field of similar to 5.6 V/mm from the pristine ZnO urchins emitter. Furthermore, the GdB6-ZnOemitter exhibits good emission stability at pre-set value of similar to 5 mA over duration of more than 3 hours. The superior FE behaviour of the GdB6-ZnO is attributed to low work-function of GdB6 and presence of nanometric protrusions on the emitter surface, further enhancing the aspect ratio provided by the ZnO urchins. The present results demonstrate a facile approach towards fabrication of high current density cold cathodes due to rare earth hexaborides via designing hetero-architectures comprised of their well adherent ultrathin coating on high aspect ratio metal oxide nanostructures.

Field emission properties of highly ordered low-aspect ratio carbon nanocup arrays - Gupta, Bipin Kumar; Kedawat, Garima; Kumar, Pawan; Singh, Satbir; Suryawanshi, Sachin R.; Agrawal, Neetu; Gupta, Govind; Kim, Ah Ra; Gupta, R. K.; More, Mahendra A.; Late, Dattatray J.; Hahm, Myung Gwan (RSC Advances, 2016)
Herein, we design and develop a field emission device utilizing highly porous carbon nanocup (CNC) films. These three-dimensional (3D) low-aspect ratio CNC structures were fabricated by a combination of anodization and chemical vapor deposition techniques. The low turn-on fields of 2.30 V mu m(-1) were observed to draw an emission current density of 1 mu A cm(-2) and a maximum emission current density of similar to 1.802 mA cm(-2) drawn at an applied field of similar to 4.20 V mu m(-1). The enhanced field emission behavior observed from the CNC films is attributed to an excellent field enhancement factor of 1645. The observed field emission properties of CNC arrays are attributed to a synergistic combination of high aspect ratio, nano-sized radius of curvature, highly organized distribution of the emitters over the whole area of specimen and lower screening effect of the CNC arrays. These observations shed light on the effect of the stacking carbon layers of CNC on their electronic properties and open up possibilities to integrate new morphologies of graphitic carbon in nanotechnology applications. Thus, the low turn on field, high emission current density and better emission current stability enable CNC based future field emission applications.

Glucose sensing and low-threshold field emission from MnCo2O4 nanosheets - Naik, Kusha Kumar; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2016)
Manganese cobalt oxide (MnCo2O4) nanosheets were grown on nickel (Ni) foam by a simple electrodeposition method. The as-synthesized nanosheets were characterized using X-ray diffraction and scanning electron microscopy. The Ni foam supports the growth of MnCo2O4 nanosheets without any aggregation, thereby increasing its catalytic and electronic properties. The electrochemical studies show that MnCo2O4 exhibits excellent electrocatalytic activity towards glucose sensing applications. The MnCo2O4 based glucose sensor shows a good sensitivity value of 8.2 mA mM(-1) cm(-2), with a response time of 19 s. In addition to this, field emission studies of as-synthesized MnCo2O4 reveal a low turn-on field value of 1.9 V mm(-1) and good emission current stability, demonstrating MnCo2O4 nanosheets as a good field emitter material.

Laser exfoliation of 2D black phosphorus nanosheets and their application as a field emitter - Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2016)
Highly crystalline two dimensional (2D) few layered black phosphorus (BP) nanosheets have been synthesized via a one step facile laser irradiation technique under optimized experimental conditions. The field emission investigations on the few layered black phosphorus nanosheets were carried out at the base pressure 1 x 10(-8) mbar. The morphological, elemental, optical, and structural analysis of the as-synthesized black phosphorus sample was carried out using SEM, AFM, EDAX, TEM, and Raman spectroscopy. The turn-on values of the BP nanosheets emitter were found to be significantly lower than that of earlier reports of BP nanosheets, graphene, and carbon nanotubes based field emitters due to the high field enhancement factor (beta) similar to 2986 associated with atomically thin/sharp edges of the BP nanosheets emitter. The emission current versus time plot depicts the good emission current stability with a pre-set value of 1 mu A for similar to 5 h duration. Our facile synthesis approach and the robust field emitter nature of the BP nanosheets makes them a potential candidate for a practical electron source in vacuum micro/nanoelectronic devices.

Low frequency noise and photo-enhanced field emission from ultrathin PbBi2Se4 nanosheets - Suryawanshi, Sachin R.; Guin, Satya N.; Chatterjee, Arindom; Kashid, Vikas; More, Mahendra A.; Late, Dattatray J.; Biswas, Kanishka (Journal of Materials Chemistry C, 2016)
Atomically thin two-dimensional layered materials have gained wide interest owing to their novel properties and potential for applications in nanoelectronic and optoelectronic devices. Here, we present the spectral analysis and photo-enhanced field emission studies of a layered intergrowth PbBi2Se4 nanosheet emitter, performed at the base pressure of similar to 1 x 10(-8) mbar. The emitter shows a turn-on field value of similar to 4.80 V mu m(-1), corresponding to an emission current density of similar to 1 mu A cm(-2). Interestingly, when the cathode was illuminated with visible light, it exhibited a lower turn-on field of B3.90 V mm(-1), and a maximum emission current density of similar to 893 mu A cm(-2) has been drawn at an applied electric field of similar to 8.40 V mu m(-1). Furthermore, the photo-enhanced emission current showed reproducible, step-like switching behavior in synchronous with ON-OFF switching of the illumination source. The emission current-time plots reveal excellent stability over a duration of similar to 6 h. Low-frequency noise is a significant limitation for the performance of nanoscale electronic devices. The spectral analysis performed on a Fast Fourier Transform (FFT) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha similar to 0.99. The low frequency noise, photo-enhanced field emission, and reproducible switching behavior characterized with very fast rise and fall times propose the layered PbBi2Se4 nanosheet emitter as a new promising candidate for novel vacuum nano-optoelectronic devices.

Low turn-on field and high field emission current density from Ag/TiO 2 nanocomposite - Patil, Girish P.; Deore, Amol B.; Bagal, Vivekanand S.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (Chemical Physics Letters, 2016)
High current density of 1.24 mA/cm2 was drawn at an applied field of 4.4 V/μm from Ag/TiO2 nanocomposite. Also the turn-on field has been reduced from 3.9 V/μm to 2.7 V/μm for the emission current density of 10 μA/cm2. Ag/TiO2 nanocomposite was synthesized by using UV-switchable reducing agent. TiO2 nanotube wall was decorated by Ag nanoparticles with average diameter of 17 nm. To the best of our knowledge this is the first report on the field emission studies of Ag/TiO2 nanocomposite. Simple synthesis route coupled with superior field emission properties indicate the possible use of Ag/TiO2 nanocomposite for micro/nanoelectronic devices.

Observation of enhanced field emission properties of Au/TiO2 nanocomposite - Patil, Girish P.; Bagal, Vivekanand S.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (Applied Physics A-Materials Science & Processing, 2016)
Simple and low-cost method of thermal annealing was used to decorate Gold (Au) nanoparticles on aligned TiO2 nanotubes. The aligned TiO2 nanotubes were decorated by Au nanoparticles with an average diameter of 9, 18 and 28 nm (aligned TiO2 nanotubes referred as specimen A and TiO2 nanotubes decorated by Au nanoparticles with average diameter of 9, 18 and 28 nm are referred as specimen B, C and D, respectively). The detailed characterization such as structural, morphological and elemental analysis of TiO2 and Au/TiO2 nanocomposite have been carried out using X-ray diffraction, field emission scanning electron microscope, transmission electron microscope, X-ray photoelectron spectroscopy and Raman spectroscopy. Furthermore, the meticulous comparative field emission characteristics of the aligned TiO2 nanotubes and Au/TiO2 nanocomposite have been performed. The turn-on field defined for the current density of 10 mu A/cm(2) has been found to be 3.9, 2.8, 3.2 and 3.7 V/mu m for specimen A, B, C and D, respectively. The observed low turn-on field of specimen B has been found to be superior than the other semiconducting nanocomposites reported in the literature. The emission current stability over a period of 3 h is found to be better for all the specimens. To the best of our knowledge, a systematic field emission study of Au/TiO2 nanocomposite has not been explored. The observed superior field emission study of Au/TiO2 nanocomposite indicates their possible use in micro/nanoelectronic devices.

Promising field electron emission performance of vertically aligned one dimensional (1D) brookite (beta) TiO2 nanorods - Devan, Rupesh S.; Ma, Yuan-Ron; More, Mahendra A.; Khare, Ruchita T.; Antad, Vivek V.; Patil, Ranjit A.; Thakare, Vishal P.; Dhayal, Rajendra S.; Schmidt-Mende, Lukas (RSC Advances, 2016)
We evidence field-electron emission (FE) studies on the large-area array of one-dimensional (1D) brookite (beta) TiO2 nanorods. The pure 1D beta-TiO2 nanorods of 10 nm width and 760 nm long were synthesized on Si substrate utilizing hot-filament metal vapor deposition technique. X-ray diffraction (XRD) and transmission electron microscopy (TEM) analysis evidenced the beta-TiO2 nanorods to be composed of orthorhombic crystals in brookite (beta) phase. X-ray photoemission spectroscopy (XPS) revealed the formation of pure stoichiometric (i.e. 1 : 1.98) 1D TiO2 nanorods. The values of turn-on field, required to draw current density of 10 mA cm(-2), was observed 3.9 V mu m(-1) for pristine 1D beta-TiO2 nanorods emitters, which were found significantly lower than doped/undoped 1D TiO2 nanostructures (i.e. nanotubes, nanowires, nanorods) based field emitters. The enhanced FE behavior of the TiO2/Si emitter can be attributed to modulation of electronic properties due to the high aspect ratio of vertically aligned TiO2 nanorods. Furthermore, the orthodox emission situation of pristine TiO2/Si emitters exhibit good emission stability and reveal their potentials as promising FE material.

Pulsed laser-deposited nanocrystalline GdB6 thin films on W and Re as field emitters - Suryawanshi, Sachin R.; Singh, Anil K.; Phase, Deodatta M.; Late, Dattatray J.; Sinha, Sucharita; More, Mahendra A. (Applied Physics A-Materials Science & Processing, 2016)
Gadolinium hexaboride (GdB6) nanocrystalline thin films were grown on tungsten (W), rhenium (Re) tips and foil substrates using optimized pulsed laser deposition (PLD) technique. The X-ray diffraction analysis reveals formation of pure, crystalline cubic phase of GdB6 on W and Re substrates, under the prevailing PLD conditions. The field emission (FE) studies of GdB6/W and GdB6/Re emitters were performed in a planar diode configuration at the base pressure similar to 10(-8) mbar. The GdB6/W and GdB6/Re tip emitters deliver high emission current densities of similar to 1.4 and 0.811 mA/cm(2) at an applied field of similar to 6.0 and 7.0 V/mu m, respectively. The Fowler-Nordheim (F-N) plots were found to be nearly linear showing metallic nature of the emitters. The noticeably high values of field enhancement factor (beta) estimated using the slopes of the F-N plots indicate that the PLD GdB6 coating on Wand Re substrates comprises of high-aspect-ratio nanostructures. Interestingly, the GdB6/W and GdB6/Re planar emitters exhibit excellent current stability at the preset values over a long-term operation, as compared to the tip emitters. Furthermore, the values of workfunction of the GdB6/W and GdB6/Re emitters, experimentally measured using ultraviolet photoelectron spectroscopy, are found to be same, similar to 1.6 +/- 0.1 eV. Despite possessing same workfunction value, the FE characteristics of the GdB6/W emitter are markedly different from that of GdB6/Re emitter, which can be attributed to the growth of GdB6 films on W and Re substrates.

Spatially branched CdS-Bi2S3 heteroarchitecture: single step hydrothermal synthesis approach with enhanced field emission performance and highly responsive broadband photodetection - Bankar, Prashant K.; Pawar, Mahendra S.; Pawbake, Amit S.; Warule, Sambhaji S.; Late, Dattatray J.; More, Mahendra A. (RSC Advances, 2016)
This report explores the controlled hierarchical synthesis of CdS nanostructure branches on Bi2S3 nanorod cores via a facile single step hydrothermal route. Morphological and structural studies reveal the formation of CdS-Bi2S3 heteroarchitecture with excellent stoichiometry between the constituent elements. The growth of CdS over Bi2S3 strongly depends on optimization of the reaction conditions, especially low PVP concentration. Furthermore, the as-synthesized CdS-Bi2S3 heteroarchitecture demonstrates multifunctionality in field emission and photoresponse. Interestingly, the CdS-Bi2S3 heteroarchitecture shows enhanced field emission properties such as low turn-on field (similar to 1.8 V mu m(-1) for 10 mu A cm(2)), high emission current density and better current stability in comparison to Bi2S3 and other nanostructures. The as-synthesized CdS-Bi2S3 heteroarchitecture exhibits considerable response and recovery times, similar to 207 ms and 315 ms, respectively in comparison to bare Bi2S3 nanostructures (similar to 655 ms and 678 ms). The present results demonstrate CdS-Bi2S3 heteroarchitecture as a potential candidate for future optoelectronic device applications.

Surface modification of aligned CdO nanosheets and their enhanced field emission properties - Bagal, Vivekanand S.; Patil, Girish P.; Deore, Amol B.; Suryawanshi, Sachin R.; Late, Dattatray J.; More, Mahendra A.; Chavan, Padmakar G. (RSC Advances, 2016)
Porous aligned CdO nanosheets were grown on a cadmium (Cd) substrate by the simple and cost effective method of thermal annealing. Further, decoration of gold (Au) nanoparticles on the porous aligned CdO nanosheets (specimen A) was achieved by coating with a Au thin film and subsequent annealing treatment. The average diameters of decorated Au nanoparticles were found to be 15 nm, 21 nm and 28 nm for the Au thin films with 20 s, 40 s and 60 s (specimens B, C, and D) coating times. Detailed characterizations, such as structural and morphological analysis of porous CdO nanosheets and Au/CdO nanocomposite (Au decorated porous CdO nanosheets), have been carried out using a Field Emission Scanning Electron Microscope (FESEM), X-ray diffraction (XRD) and a Transmission Electron Microscope (TEM). Field emission studies of specimens A, B, C and D were carried out in the planar diode configuration. Turn-on fields of 1.9 V mu m(-1), 1.1 V mu m(-1), 2.4 V mu m(-1) and 2.8 V mu m(-1) have been found for the emission current density of 10 RA cm(-2) for specimens A, B, C and D, respectively. The observed low turn -on field of specimen B (Au diameter of 15 nm) was found to be superior to other semiconducting nanostructures reported in the literature. The field emission current stability over a period of 3 h at the preset current density of 1 RA cm(-2) is found to be excellent for all specimens. To the best of our knowledge, field emission studies along with surface modification of porous aligned CdO nanosheets have not been reported in the literature. The simple synthesis route, facile surface modification and the superior field emission results make the present emitter very suitable for micro/nano electronic devices.

Synthesis, microstructure, optical and field emission studies of iron vanadium oxide nanosheets - Badadhe, Satish S.; Suryawanshi, Sachin R.; Naphade, Rounak A.; Chaudhary, Minakshi V.; More, Mahendra A.; Shelke, Manjusha V.; Ogale, Satishchandra B. (Journal of Physics D-Applied Physics, 2016)
We report a single step growth of thin graphene-like, densely packed FeV3O8 (FVO) nanosheets on silicon substrates via facile hydrothermal synthesis. These nanosheets have dimensions of a few microns with thin edges, offering very high aspect ratio. These FVO nanosheets exhibit excellent field emission behaviour with low turn on and threshold voltages of 1.3 V mu m(-1) and 1.7 V mu m(-1), respectively. The corresponding emitter delivers high emission current density of (similar to 1.650 mA cm(-2)) at fairly low applied field (similar to 4.00 V mu m(-1)).
Keywords: FeV3O8; field emission; nanosheets

Synthesis of Ni-doped ZnO nanostructures by low-temperature wet chemical method and their enhanced field emission properties - Rana, Amit Kumar; Bankar, Prashant; Kumar, Yogendra; More, Mahendra A.; Late, Dattatray J.; Shirage, Parasharam M. (RSC Advances, 2016)
In this study, we report an enhancement in the field emission (FE) properties of ZnO nanostructures obtained by doping with Ni at a base pressure of similar to 1 x 10(-8) mbar, which were grown by a simple wet chemical process. The ZnO nanostructures exhibited a single-crystalline wurtzite structure up to a Ni doping level of 10%. FESEM showed a change in the morphology of the nanostructures from thick nanoneedles to nanoflakes via thin nanorods with an increase in the Ni doping level in ZnO. The turn-on field required to generate a field emission (FE) current density of 1 mu A cm(-2) was found to be 2.5, 2.3, 1.8 and 1.7 V mu mcm(-2) for ZnO (Ni0%), ZnO (Ni5%), ZnO (Ni7.5%) and ZnO (Ni10%), respectively. A maximum current density of similar to 872 mu A cm(-2) was achievable, which was generated at an applied field of 3.1 V mu m cm(-2) for a Ni doping level of 10% in ZnO. Long-term operational current stability was recorded at a preset value of 5 mA for a duration of 3 h and was found to be very high. The experimental results indicate that Ni-doped ZnO-based field emitters can open up many opportunities for their potential use as an electron source in flat panel displays, transmission electron microscopy, and the generation of X-rays. Thus, the simple low-temperature (similar to 80 degrees C) wet chemical synthesis approach and the robust nature of the ZnO nanostructure field emitter can provide prospects for the future development of cost-effective electron sources.

Enhanced field emission characteristics of a 3D hierarchical Hfo2-Zno heteroarchitecture - Shisode, Raju T.; Suryawanshi, Sachin R.; Mistari, Chetan D.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
Three dimensional (3D) HfO2-ZnO heteroarchitecture comprised of thin coating of HfO2 on self assembled 3D ZnO urchins with pointed apex has been synthesized using hydrothermal route followed by Pulsed Laser Deposition (PLD). The as-synthesized HfO2-ZnO heteroarchitecture was characterized using XRD, SEM, EDS, and (HR) TEM, in order to reveal its structural, morphological, and chemical properties. The HfO2-ZnO heteroarchitecture emitter exhibits superior field emission (FE) behaviour in contrast to the pristine ZnO urchins, demonstrated by delivery of high emission current density of similar to 885 mA/cm2 at an applied field of similar to 3.35 V/mm, against similar to 383 mA/cm(2) at an applied field of similar to 4.32 V/mu m for the pristine ZnO urchins emitter. Interestingly, the HfO2-ZnO heteroarchitecture emitter exhibits excellent emission current stability characterized with fewer fluctuations, owing to very good ion-bombardment resistance offered by the HfO2 coating. Furthermore, the heteroarchitecture thus obtained facilitates tailoring of the morphology with high aspect ratio and modulation of electronic properties as well, thereby enhancing the FE behaviour. Despite HfO2 being wide band gap and high-k material, the HfO2-ZnO heteroarchitecture exhibits potential as promising candidate for fabrication of high current density cold cathode
Keywords: 3D heteroarchitecture; Field Emission (FE); hydrothermal; PLD; TEM

Enhanced field emission performance of MoO3 nanorods and MoO3-rGO nanocomposite - Bankar, Prashant K.; Khandare, Lina N.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
The graphene and semiconducting hybrid based nanostructures have emerged as a new class of multifunctional materials with improved performance in comparison to the pristine semiconductors. Here, as-synthesized MoO3-reduced graphene oxide (rGO) nanocomposite emitter exhibits enhanced field emission (FE) behavior as compared to the pristine 1D MoO3 nanorods. The hydrothermally synthesized 1D MoO3 nanorods (1D) are grafted on the rGO sheet (2D) using a simple room temperature sonochemical method. The morphological and structural analysis confirms the attachment of MoO3 nanorods with rGO and the improved conductivity of the sample indicates a strong electronic interaction between them. Furthermore, the FE studies of as-synthesized MoO3 nanorods and MoO3-rGO nanocomposite emitters, carried out at a base pressure -1 x 10(-8) mbar, reveals the values of turn on field (required to draw an emission current density of 1 mu A/cm(2)) as 1.6 and 1.4 V/mu m, respectively. Interestingly, the maximum emission current density of 2810 mA/cm(2) is achieved at a lower applied field of 2.7 V/mu m from the MoO3-rGO nanocomposite emitter. The enhancement in FE performance of MoO3-rGO nanocomposite is attributed to the improved electrical conductivity, mechanical properties and higher concentration of protruding edges (emission sites). This observation can be extended to other graphene-based 1D inorganic hybrid semiconductor nanocomposites, which can provide a valuable opportunity to explore novel hybrid materials for vacuum nano-electronic devices.

Enhanced field emission performance of NiMoO4 nanosheets by tuning the phase - Bankar, Prashant K.; Ratha, Satyajit; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (Applied Surface Science, 2017)
In this paper we report, large scale synthesis of a and beta-NiMoO4 by a facile hydrothermal method and we observed that urea plays important role on the growth of beta-NiMoO4 nanosheets. We have also carried out field emission (FE) investigations of alpha and beta-NiMoO4 at a base pressure of similar to 1 x 10(-8) mbar. The obtained turn-on field at emission current density of 1 mu A/cm(2) for beta-NiMoO4 nanosheets and alpha-NiMoO4 is 1.3V/mu m and 2.2V/mu m respectively were observed. The maximum field emission current density of 1.006 mA/cm(2) at an applied electric field of 2.7V/mu m was achieved for beta-NiMoO4 nanosheets. Furthermore, we found that the beta-NiMoO4 nanosheets possess good field emission performance compared to alpha-NiMoO4. The results indicate that NiMoO4 can be used as a promising material in FE applications with possibility of tuning field emission performance by controlling the phase. (C) 2017 Elsevier B.V. All rights reserved.

Extraction of the very high tunneling current and extremely stable emission current from GdB6/W-tip source synthesized using arc plasma - Suryawanshi, Sachin R.; Kanhe, Nilesh; Mathe, Vikas L.; Phase, Deodatta M.; Late, Dattatray J.; More, Mahendra A. (ChemistrySelect, 2017)
Herein, we report the one step arc plasma synthesis of the GdB6 (Gadolinium hexaboride) nanoparticles and its field emission (FE) characteristics on tungsten point substrate (GdB6/ W). The SEM /TEM analysis revealed the GdB6 nanoparticles on W point substrate exhibit irregular shaped, grainy, dense, course morphology, i.e. uniformly covering the entire tip substrate surface. For GdB6/W point source, the values of the turn-on and threshold fields, defined as field required to draw an emission current density similar to 1 mA/cm(2) and similar to 100 mA/cm(2), respectively are found to be similar to 2.2 and similar to 2.7 V/mm, for anodecathode separation of similar to 1 mm. Interestingly, a very high emission current density of similar to 3.5 A/cm(2) has been drawn from the GdB6/W point emitter at relatively lower applied field of similar to 6.4 V/mm. The field enhancement factor found to be similar to 10,250. The GdB6/W point electron source exhibits a good emission current stability at similar to 10 mA for a period of 6 hr. The emission current stability is enumerated in terms of standard deviation and its magnitude has been measured to be only 1.72% with respect to the average value. The superlative field emission characteristics signify the GdB6/W point electron source as potential candidates for vacuum micro/nanoelectronics device applications.
Keywords: Arc Plasma; field emission; Thin films

PbS nanostar-like structures as field emitters - Pawar, Mahendra S.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (Chemistryselect, 2017)
The crystalline PbS nanostars were synthesized by thermal decomposition of thioacetamide (TAA) in aqueous solutions of lead acetate and acetic acid at 80 8 degrees C. The structure and morphology of the PbS nanostars have been characterized using X-Ray Diffraction (XRD), Raman Spectroscopy, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). The optical properties of the PbS nanostars have been studied using UV-Visible absorption Spectroscopy (UVVis). The field emission investigations have been carried out on the as synthesized PbS nanostars at the base pressure of similar to 13 10(-8) mbar. The turn on field required to draw an emission current density of 1 mu A/cm(2) is found to be 1.8 V/mm. The emission current-time plots show good emission current stability of the PbS nanostar emitter over a period of 4 hrs. The results in terms of low turn-on field and long term emission current stability of the PbS nanostars emitter reveals that it can be used in field emission based vacuum microelectronics / nanoelectronic devices.

High-performance field emission device utilizing vertically aligned carbon nanotubes-based pillar architectures - Gupta, Bipin Kumar; Kedawat, Garima; Gangwar, Amit Kumar; Nagpal, Kanika; Kashyap, Pradeep Kumar; Srivastava, Shubhda; Singh, Satbir; Kumar, Pawan; Suryawanshi, Sachin R.; Seo, Deok Min; Tripathi, Prashant; More, Mahendra A.; et al. (AIP Advances, 2018)
The vertical aligned carbon nanotubes (CNTs)-based pillar architectures were created on laminated silicon oxide/silicon (SiO2/Si) wafer substrate at 775 degrees C by using water-assisted chemical vapor deposition under low pressure process condition. The lamination was carried out by aluminum (Al, 10.0 nm thickness) as a barrier layer and iron (Fe, 1.5 nm thickness) as a catalyst precursor layer sequentially on a silicon wafer substrate. Scanning electron microscope (SEM) images show that synthesized CNTs are vertically aligned and uniformly distributed with a high density. The CNTs have approximately 2-30 walls with an inner diameter of 3-8 nm. Raman spectrum analysis shows G-band at 1580 cm(-1) and D-band at 1340 cm(-1). The G-band is higher than D-band, which indicates that CNTs are highly graphitized. The field emission analysis of the CNTs revealed high field emission current density (4mA/cm(2) at 1.2V/mu m), low turn-on field (0.6 V/mu m) and field enhancement factor (6917) with better stability and longer lifetime. Emitter morphology resulting in improved promising field emission performances, which is a crucial factor for the fabrication of pillared shaped vertical aligned CNTs bundles as practical electron sources. (c) 2018 Author(s).

Development of pristine and Au-decorated Bi2O3/Bi2WO6 nanocomposites for supercapacitor electrodes - Gote, Gorkshnath H.; Pathak, Mansi; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2019)
Pristine and Au-decorated Bi2O3/Bi2WO6 nanocomposites were synthesized via a facile hydrothermal method. Characterization techniques such as XRD, FESEM, HRTEM and XPS were used to explore the structural, morphological and electronic properties. Furthermore, electrochemical characterizations including cyclic voltammetry (CV), the galvanostatic charge-discharge (GCD) method, and electrochemical impedance spectroscopy (EIS) were performed to investigate the supercapacitance behaviour of the synthesized materials. Interestingly, the Au-decorated Bi2O3/Bi2WO6 nanocomposite showed a higher capacitance of 495.05 F g(-1) (1 M aqueous KOH electrolyte) with improved cycling stability (99.26%) over 2000 cycles, measured at a current density of 1 A g(-1), when compared to the pristine Bi2O3/Bi2WO6 composite (capacitance of 148.81 F g(-1) and good cycling stability (95.99%) over 2000 cycles at a current density of 1 A g(-1)). The results clearly reveal that the decoration of the Bi2O3/Bi2WO6 composite with Au nanoparticles enhances its supercapacitance behaviour, which can be attributed to an increase in electrical conductivity, good electrical contact between the electrode and electrolyte, and an increase in effective area. The Au-decorated Bi2O3/Bi2WO6 nanocomposite can be considered as an electrode material for supercapacitor application.

Graphene nanosheets assisted carbon hollow cylinder for high-performance field emission applications - Tripathi, Prashant; Gupta, Bipin Kumar; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J.; Srivastava, Onkar Nath (Materials Research Express, 2019)
Electron sources are critical constituents for myriad many electronic applications including electron imaging, mass spectroscopy etc. Here, we report the realization of high-performance field emission from graphene assisted carbon hollow cylinders (Gr-CHCs) composed of multi-stacked radially aligned CNTs. These CHCs have built-in synthesis related Fe nanoparticles (NPs). This engineered nano-structure exhibits excellent field emission properties such as one of the ultra-low turn-on field (0.64V mu m(-1) at 10 mu A cm(-2)), low threshold field (0.74V mu m(-1) at 100 mu A cm(-2)), very high current density (15.49 mA cm(-2) at 1.32V mu m(-1)) which is nearly double the current density obtained in our previous study. High field enhancement factor (0.72. x. 10(4)) with highly stable emission current at 100 mu A was observed for more than 3 hrs at the base pressure of similar to 1. x. 10(-8) mbar. This study suggests an approach to enhance the current density using the proposed innovative nanostructure and forms the basic theme of this communication. Highly efficient and stable field emissions observed are attributed to the geometry of cylinder and the production of the high density of sharp protrusions within the graphene sheets which enhance the local electric field and dramatically enhance field emission. This innovative cylindrical geometry associated with graphene assisted on Fe bearing aligned CNTs along with the periphery of the bulk cylinder provides an easy injection of electrons from the conduction band of CHCs into the vacuum in the presence of an external electric field. The tunability of field emission properties of these CHCs can be easily achieved by tailoring their diameter (10 and 20 mm) and different concentrations of the precursor. This new approach of the graphene assisted cylindrical geometry-based field emitter source provides enormous prospects and demand for next-generation high resolutions display devices.
Keywords: Carbon nanotubes; field emission; graphene assisted carbon hollow cylinder; protrusions

Realization of efficient field emitter based on reduced graphene oxide-Bi2S3 heterostructures - Gote, Gorkshnath H.; Bhopale, Somnath R.; More, Mahendra A.; Late, Dattatray J. (Physica Status Solidi A-Applications and Materials Science, 2019)
Herein, Bi2S3 nanorods and reduced graphene oxide (rGO)-Bi2S3 heterostructures are synthesized using a simple hydrothermal method. The structural, morphological, chemical, and elemental analysis of as-synthesized materials is performed using X-ray diffraction (XRD), Raman spectroscopy, field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Field emission (FE) studies are carried out on both pristine Bi2S3 nanorods and rGO-Bi2S3 heterostructure samples at a base pressure of approximate to 1 x 10(-8) mbar. The results show that the rGO-Bi2S3 heterostructure emitter has superior FE performance compared to pristine Bi2S3 emitters in terms of the turn-on field (2.6 V mu m(-1) at 10 mu A cm(-2)) and threshold field (4.0 V mu m(-1) at 100 mu A cm(-2)) along with a high emission current density of approximate to 1464 mu A cm(-2) at an applied electric field of 7.0 V mu m(-1). The rGO-Bi2S3 heterostructure emitter exhibits very good emission current stability, tested for more than 3 h duration, characterized by standard deviation values approximate to 2.84 and 4.06, corresponding to preset values 12 and 100 mu A. This study implies that one-step hydrothermal route can be efficiently used to synthesize organic-inorganic heterostructures that possess unique morphology. Furthermore, the synthesized rGO-Bi2S3 heterostructure emitter shows potential as an electron source for practical application in vacuum microelectronic devices.
Keywords: Bi2S3; field emission; Heterostructures; Nanorods; Reduced graphene oxide

Enhanced field emission behaviour from ethylene glycol mediated synthesis of 2D hexagonal SnS2 disc with nanoparticle - Mutadak, Pallavi R.; Chaudhari, Nilima S.; Gadhave, Dattatraya C.; Rajput, Parikshit K.; Kolekar, Sadhu K.; Late, Dattatray J.; More, Mahendra A.; Warule, Sambhaji S. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2022)
Herein, octahedron and stacked 2D hexagonal disc - like nanostructures of SnS2 were obtained by hydrothermal and ethylene glycol mediated hydrothermal methods, respectively. Attempt has been made to shade light on the plausible growth mechanism. Liquid phase exfoliation followed by centrifugation process leads to presence of tiny single crystalline SnS2 nanoparticles (similar to 5 nm) on the hexagonal discs over C substrate, characterized by preferred growth along {001} direction. The observed Raman shift and enhanced intensities of A(1g) and E-g modes infer charge interactions between the SnS2 disc and C substrate. Interestingly, the SnS2-C emitter exhibited superior field emission (FE) behaviour due to the unique morphology, excellent charge transfer, and reduced work function (similar to 4.1 eV). Here the extraction of large current density of similar to 1137 mu A/cm(2) at an applied field of 3.72 V/mu m, with good emission current stability. The present strategy is beneficial to design architectured morphology for multi-functionality.
Keywords: 2D layered materials; Field Emission (FE); SnS2; SnS2 on C

Facile synthesis of nanocomposites of CNF-Sn and C-Sn microspheres: Prospective field emitter - Badadhe, Satish S.; Yadav, Poonam; Suryawanshi, Sachin; More, Mahendra A. (Journal of Alloys and Compounds, 2022)
We report synthesis of Carbon nanofibers (CNFs) and hybrid nanocomposites namely, CNF-Sn and C-Sn microspheres using simple electrospinning technique, followed by annealing in controlled atmosphere. The as-prepared materials were characterized using X-raydiffraction (XRD), Field emission scanning electron microscopy (FESEM), Transmission electron microscopy (TEM), Ultra-violet photoelectron spectroscopy (UPS), and Raman spectroscopy to reveal their physico-chemical properties. As carbon family members are potential materials for field emission (FE) based applications, owing to their high aspect ratio FE characteristics of the synthesized materials were explored at base pressure of 1 x 10(-8) mbar. Interestingly, the hybrid nanocomposite CNF-Sn and C-Sn emitters showed improved FE behavior (with the turn-on field of 3.4 and 1.36 V/mu m, respectively) in contrast to the pristine CNFs emitter (turn-on field of 5.4 V/mu m). Furthermore, the maximum emission current density is substantially enhanced, 7.75 and 4.6 mA/cm(2) for CNF-Sn and C-Sn emitters, respectively. The improvement in the FE behavior of nanocomposite emitters is attributed to the combined effect of morphology and modulation of electronic properties at the interface of nanocomposites. The results confirm that FE characteristics of pristine nanostructures can be greatly improved upon formation of their nanocomposites and this approach can be extended to other nanostructures for improving their multi-functionalities. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: carbon nanofiber; electrospinning; field emission; Nanocomposite; Tin

Titanium trisulfide nanosheets and nanoribbons for field emission- based nanodevices - Pawbake, Amit S.; Khare, Ruchita T.; Island, Joshua O.; Flores, Eduardo; Ares, Jose R.; Sanchez, Carlos; Ferrer, Isabel J.; Pawar, Mahendra; Frank, Otakar; More, Mahendra A.; van der Zant, Herre S. J.; Castellanos-Gomez, Andres; et al. (ACS Applied Nano Materials, 2023)
The field emission (FE) properties of TiS3 nanosheets and nanoribbons, synthesized by direct sulfuration of bulk titanium, are investigated. The nanosheets show an enhanced FE behavior with a low turn-on field of similar to 0.3 V/ mu m, required for drawing an emission current density of similar to 10 mu A/cm2. Interestingly, the TiS3 nanosheet emitter delivered a large emission current density of similar to 0.9 mA/ cm2 at a relatively low applied electric field of similar to 0.4 V/mu m. We have estimated the values of the field enhancement factor (beta), which are found to be similar to 5 x 104 for the TiS3 nanosheet emitter and similar to 4 x 103 for the nanoribbon emitter. We attribute the superior FE performance to the presence of atomically sharp edges and the reduced thickness of TiS3, as reflected in the high value of beta. In fact, the nanosheet sample presents a higher density of ultrathin layers (similar to 12 nm-thick), and thus, they have a larger edge to volume ratio than the nanoribbon samples (which are similar to 19 nm-thick). The superior FE behavior of TiS3 nanosheets over nanoribbons makes them a propitious field emitter and can be utilized for various FE-based applications, demanding large emission currents and lower operational voltages. Moreover, the FE current stability recorded on these samples confirms their promising performance. Thus, the present investigation brings out a great promise of TiS3 nanosheets and nanoribbons as field emitters for vacuum nanoelectronics devices.
Keywords: Current stability; field emission; nanoribbon; nanosheets; TiS3